Towards a quantitative indicator of feather disruption following the cleansing of oiled birds. Issue 1 (15th July 2017) - Bigger, Stephen W.; Ngeh, Lawrence N.; Dann, Peter; Orbell, John D.
Abstract: A computer-based imaging method for determining feather microstructure coherency following a cleansing treatment, was developed, calibrated and trialled on Mallard Duck ( Anas platyrhyhchos ) feathers. The feathers were initially contaminated with a light crude oil and then cleansed by either detergent (Deacon 90) treatment or, alternatively, by magnetic particle technology (MPT) using iron powder. The imaging method provides a single quantitative parameter for the coherence of feather microstructure and the results confirm that MPT treatment imparts less disruption to the feather microstructure than detergent treatment. It is proposed that this imaging method can be developed and implemented for the assessment of feather disruption and possibly damage, either for the trialling of different treatment protocols, or as a tool during the rehabilitation process, along with other such indicators, to give a more comprehensive assessment of feather condition than is currently available. Highlights: Computer-based imaging method developed to quantitatively assess feather coherency. Imaging method successfully applied in studying cleansing of oil-soaked feathers and to feather coherency assessment. Cleansing feathers magnetically imparts less disruption to feather integrity than detergent methods.